Uji Efektivitas Gel Ekstrak Daun Jarak Pagar (Jatropha Curcas L.) sebagai Penyembuhan Luka Sayat - Vera Estefania Kaban; Ginting, Junius Gian; Nasri, Nasri; Sagala, Hasel Untung Bersinar; Tarigan, Serly Annisa Br (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Indonesia is known for having abundant biological riches and many plants that can be used as medicine. One of the medicinal plants that is often used by Indonesian people is Jatropha curcas leaves. Jatropha plants are currently used as traditional medicine to treat wounds. One common medication used for cuts is povidone iodine which is effective against bacterial infections. However, povidone iodine also has side effects such as irritation, toxic reactions and burning skin. Jatropha leaves have strong antioxidant activity, so it is necessary to innovate in wound treatment using natural ingredients in the form of gel preparations. The gel preparation was chosen because it is practical, not sticky, easily absorbed by the skin, and works directly on wound tissue. The aim of this study was to assess how well a gel made from ethanol extract of jatropha leaves accelerates the healing of cut wounds in white mice. Jatropha curcas leaves were extracted using the maceration method using 96% ethanol as the solvent. Gel stability testing was carried out organoleptically, homogeneity test and spreadability test. Jatropha leaf extract gel was tested on mice that had been given incisions 1.4 cm long with formulations of 10%, 15% and 20% jatropha leaf extract concentrations. Observations were carried out for seven days. Research findings showed that giving white rats gel containing jatropha leaf extract significantly accelerated their ability to repair wounds